Strategic priorities and challenges in research software funding: Results from an international survey [version 2; peer review: 2 approved, 1 approved with reservations, 1 not approved] - Daniel S. Katz; Eric A. Jensen (F1000Research)
Background Research software is increasingly recognized as critical infrastructure in contemporary science. It spans a broad spectrum, including source code files, algorithms, scripts, computational workflows, and executables, all created for or during research. While research funders have developed programs, initiatives, and policies to bolster research software’s role, there has been no empirical study of how these funders prioritize support for research software. Understanding their priorities is essential to clarify where current support is concentrated and to identify strategic gaps. Methods We conducted an online mixed methods survey of international research funders (n=36) to explore their priorities in supporting research software. The survey gathered data on the specific outcomes funders emphasize in their programs and initiatives for research software. Results The survey revealed that funders place strong emphasis on developing skills, promoting software sustainability, embedding open science practices, building community and collaboration, advancing research software funding mechanisms, increasing software visibility and use, fostering innovation, and ensuring security. Conclusions The findings highlight opportunities to enhance research software’s role through increased funder attention on professional recognition for software contributions and the non-technical, social aspects of research software sustainability. Addressing these areas could lead to more effective support and development of research software, ultimately benefitting the entire research ecosystem.